2021
DOI: 10.1177/13623613211026754
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported camouflaging behaviours used by autistic adults during everyday social interactions

Abstract: Autistic people may camouflage their innate autistic social behaviours to adapt to, cope within and/or influence the predominately neurotypical social landscape. This study describes behaviours exhibited, altered or avoided by autistic adults whilst camouflaging (i.e. camouflaging behaviours). Using Interpersonal Process Recall methodology, 17 autistic adults (8 women, 6 men and 3 agender/gender neutral individuals) participated in a brief social task designed to replicate a common day-to-day social situation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 108 publications
2
33
0
3
Order By: Relevance
“…Results suggest that social pressures on autistic people to supress or alter stims, may reduce their ability to cope with day-to-day challenges. These findings are in keeping with previous studies which have shown that autistic people frequently supress stims and repetitive behaviours to be more socially acceptable and that doing so was detrimental to the individual (Cook et al, 2021;Hull et al, 2017;Livingston et al, 2018;Manor-Binyamini & Schreiber-Divon, 2019). Previous studies on masking (including masking stims) suggest that masking is exhausting, stressful and associated with high levels of anxiety (Bradley et al, 2021;Livingston et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Results suggest that social pressures on autistic people to supress or alter stims, may reduce their ability to cope with day-to-day challenges. These findings are in keeping with previous studies which have shown that autistic people frequently supress stims and repetitive behaviours to be more socially acceptable and that doing so was detrimental to the individual (Cook et al, 2021;Hull et al, 2017;Livingston et al, 2018;Manor-Binyamini & Schreiber-Divon, 2019). Previous studies on masking (including masking stims) suggest that masking is exhausting, stressful and associated with high levels of anxiety (Bradley et al, 2021;Livingston et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Camouflage was assessed using different measures. The most common tool (eight studies) was the Camouflaging Autistic Traits Questionnaire (CAT-Q) ( 26–31 , 36 , 39 ) which is a 25-item self-report questionnaire developed in 2018 by Hull et al ( 17 ). One study utilized a 31-item Compensation Checklist to evaluate strategies including masking, shallow compensation, deep compensation, and accommodation in participants ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the online process of understanding the mental states of a conversational partner is a relatively intuitive process for non-autistic people, but autistic people may need to engage in effortful compensatory strategies ( Livingston et al, 2020 ). Autistic people may also engage in effortful behaviours aimed at masking autistic social tendencies, which could include suppressing repetitive behaviours, carefully monitoring their eye contact, or using behavioural rules or conversational scripts to guide social behaviour ( Livingston et al, 2019b ; Cook et al, 2021a , b ). Attending to such strategies during conversation may deplete the attentional resources available to autistic people for attending to IS-relevant cues, leading to reduced IS during the interaction.…”
Section: Part 2 – Interpersonal Synchrony In Autismmentioning
confidence: 99%